Sosialisasi Pengenalan Pentingnya Cyber Security Bagi Siswa Untuk Membangun Keamanan Informasi Dalam Era Digital - Amin Hidayat; Yuda Samudra; Lely Panca Andriyanto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The rapid development of technology not only provides benefits for its users, but also provides a real threat of crime against its users, some examples of cybercrime cases that are currently busy include: fraud via chat under the guise of a photo of an item package, fraudulent chat wedding invitations, fraudulent transfer fees banks, then the most common one is lottery fraud. This community service activity held at SMA-IT Alia Islamic School aims to make students more aware of the dangers of possibilities that can occur from cybercrime. The importance of understanding youth and society regarding security on the internet or often referred to as Cyber Security is very necessary to know what threats may arise and how to deal with these threats. By understanding the threats posed, youth/students and the public are also required to know how to secure personal data on the internet. The form of this PkM activity is in the form of presentation of material related to the introduction of the importance of Cyber Security, then explaining several examples of cases of cybercrime and how to react to it as well as additional material related to the introduction of career opportunities in the field of IT, especially in Cyber Security which is then followed by a question and answer session for PkM activity participants carried out in the Language Lab room at SMA-IT Alia Islamic School.